Business and corporate aviation management - Sheehan, John J. (New York : McGraw-Hill Education, 2013)
"A one-of-a-kind, up-to-date guide to skillfully blending business and aviation issues to provide solid decision-making strategies and smart operating practices for the establishment and management of business aircraft"--Provided by publisher.
Keywords: Local service airlines -- Management; Airlines -- Management; Airports -- Management; Aeronautics -- Flights -- Management; Aeronautics, Commercial -- Management; Aeronautics, Commercial -- Charters; Airplanes, Company; Private flying; Business travel